Algae-laden water treatment with ultrafiltration: effects of moderate oxidation by Fe(ii)/permanganate on hydraulically irreversible fouling and deposition of iron and manganese oxides. Issue 1 (18th November 2020) - Qu, Fangshu; Yang, Zhimeng; Yu, Huarong; Zhou, Hong; Fan, Gongduan; He, Junguo; Rong, Hongwei
Abstract : Application of ultrafiltration (UF) in algae-laden water treatment is hindered by severe fouling and low retention of soluble organics. Abstract : Application of ultrafiltration (UF) in algae-laden water treatment is hindered by severe fouling and low retention of soluble organics. In this study, moderate oxidation by Fe(ii )/permanganate was investigated as a pretreatment for algae-laden water before UF in comparison with permanganate oxidation alone and Fe(ii ) coagulation alone. Filtration tests were performed to assess the impacts of moderate oxidation on fouling reversibility, fouling mechanisms and compositions of the fouling layers. The results showed that Fe(ii )/permanganate substantially alleviated the flux reduction by 65% and reduced reversible resistances by nearly 2 orders of magnitude, because the agglomerates formed by foulants and in situ formed iron and manganese oxides were larger in size than the algal cells, resulting in more porous fouling layers. The fouling mechanism shifted from the dual mechanism of successive pore blocking and cake filtration to single standard blocking over the whole duration investigated. However, irreversible fouling was aggravated by Fe(ii )/permanganate, because the cake filtration was weakened and the adhesion of EOM on the membrane was aggravated in the presence of in situ formed iron and manganese oxides. The iron and manganese oxides deposited in the external fouling layer rather than inside the membrane. The amounts of Fe and Mn in the fouling layer substantially increased by more than 4 times with Fe(ii )/permanganate than with permanganate or Fe(ii ). Fe(ii )/permanganate increased the removal of EOM (67%) by UF, attributing the enhanced adsorption of EOM to both the membrane and the agglomerates.